Mauritius : Technical Assistance Report-Towards Accrual Accounting and the Adoption of International Standards. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses the technical advice and recommendations of the IMF mission to the authorities of Mauritius regarding implementation of an accrual accounting framework and the adoption of international standards. It is recommended that the International Public Sector Accounting Standards be applied by all public sector entities unless the primary objective of the entity is return on investor equity. This will simplify the framework and the implementation effort and will lead to efficiencies in the preparation of consolidated financial statements. Moreover, the accrual financial statements should be compared and reconciled with budget and budgetary reports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet